The Influence of Good Corporate Governance on the Profitability of Mining Companies Listed on The Stock Exchange Indonesia Period 2013-2016 - Ayu Fitria; Siti Hayati Efi Friantin; Tri Nurdyastuti (ADVANCE, 2018)
The purpose of this research is to analyze and to provide empirical evidence of the influence of Good Corporate Governance on the profitability of mining companies listed on the IDX period 2013-2016. Population of this research is all mining companies in Indonesia. Sampling method used in this research is purposive sampling. Type and data source obtained from secondary data source. The total samples used in this research are 8 mining companies during the period 2013-2016. Analytical techniques in this research include descriptive statistics, multiple regression analysis, classical assumption testing and hypothesis testing. Based on the results of data testing show that the result of classical assumptions of this research is normally distributed, does not occur multikolonieritas, heteroskesdastisitas and autocorrelation. The results of multiple linear regression analysis and t test indicate that the Board of Directors has significant positive effect, Managerial Ownership has a significant negative effect, while Institutional Ownership, Independent Commissioner have positives but do not have significant effect on Company Profitability. Based on the result of R2 is 21.8% indicates independent variable capability, independent commissioner, managerial ownership, institutional ownership and board of directors in explaining the dependent variable that is company profitability (ROA), while the rest equal to 78,2% explained from other variable that not include in this research.Keyword : Good Corporate Governance (GCG), Company size, Profitability